An ethnographic approach to peacebuilding: understanding local experiences in transitional states - Millar, Gearoid (Studies in Conflict, Development and Peacebuilding, 2014)
Introduction 1. - Part 1: Introduction to the Ethnographic Approach . - 1. Peacebuilding, Empowerment, and Evaluation 13. - 2. Historical, Political, and Social Context 26. - Part 2: The Four Pillars of the Ethnographic Approach . - 3. Peacebuilding as Experiential 45. - 4. Ethnographic Preparation 63. - 5. Local Engagement 81. - 6. Appraisal of One's Own Implicit Assumptions 99. - Part 3: The Details and Challenges of Incorporating the Ethnographic Approach . - 7. Challenges to the Ethnographic Approach 119. - 8. The Distinctive Strengths of the Ethnographic Approach 137. - 9. Conclusion 156